Development of Virtual Laboratory as Multimedia Innovation for Interactive Learning on Reaction Rate Materials to Improve Students' Science Process Skills - Selviana, Elfa; Danu Devasyah, Mochammad; Febriana Sari, Hilmalia; Novita, Dian (JCER (Journal of Chemistry Education Research), 2023)
This research aim to produce a Multimedia Virtual Laboratory on the Reaction Rate Material to train Science Process Skills on the sub-materials of factors that affect reaction rates. The research method used is Research and Development (R&D). The results of the content validation was 91.67%, construct validation was 97.23%, validation related to presentation was 97.23%, validation related to language was 95.84% with very valid criteria. The results of the student response questionnaire stated that the average percentage of responses was 91.25% which could be categorized very practice. The results of the pre-test and post-test scores based on the t-test obtained the value of Sig. (2-tailed) 0.00 < 0.05, as well as the N-Gain analysis score of 0.93 > 0.7 with a high category so that it can be said that the Multimedia Virtual Laboratory developed is effectively used to train students' science process skills.